The role of multidisciplinary meetings for benign pancreatobiliary diseases: a tertiary centre experience. Issue 3 (5th September 2016) - Bekkali, Noor L H; Murray, Sam; Winter, Lesley; Sehgal, Vinay; Webster, George J M; Chapman, Michael H; Bandula, Steven; Amin, Zahir; Read, Samantha; Pereira, Stephen P; Johnson, Gavin J
Abstract : Multidisciplinary meetings are central to the management of chronic and complex diseases and they have become widely established across the modern healthcare. Patients with pancreatobiliary diseases can often present with complex clinical dilemmas, which fall out with the scope of current guidelines. Therefore, these patients require a personalised management approach discussed in a multidisciplinary meeting.